2018
DOI: 10.30848/pjb2019-1(46)
|View full text |Cite
|
Sign up to set email alerts
|

Effect of homeopathic nematicide pellets on plant-nematode interaction under controlled conditions

Abstract: An experiment was conducted at Department of Botany, University of Karachi to explore the efficacy of homeopathic drug pellets for the control of root knot nematode and improved plant growth of crops. Homeopathic drug pellets of Santonine-43 and Kent-20 used at 75% concentration, respectively, showed excellent results in the control of M. javanica infection but also improved the plant height, weight and yield of all tested crops such as mung bean, mash bean, okra and sunflower followed by 50% concentration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Recently, homeopathic pellets showed positive results in killing the J 2 of Meloidogyne javanica on agricultural field. Soil amended with homeopathic pellets (Kent-20 used at 75% v/w concentration) produced healthy seedlings of okra, sunflower, mung and mash bean as it suppressed the M. javanica infection as compared to control (non-amended with homeopathic pellets) which produced galls on roots and disrupt the growth of tested crops (Hanif and Dawar, 2019). Experimental researches on the principle of homeopathy in plants were mostly performed by Mexico, India, Europe and Brazil recently (Marques et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, homeopathic pellets showed positive results in killing the J 2 of Meloidogyne javanica on agricultural field. Soil amended with homeopathic pellets (Kent-20 used at 75% v/w concentration) produced healthy seedlings of okra, sunflower, mung and mash bean as it suppressed the M. javanica infection as compared to control (non-amended with homeopathic pellets) which produced galls on roots and disrupt the growth of tested crops (Hanif and Dawar, 2019). Experimental researches on the principle of homeopathy in plants were mostly performed by Mexico, India, Europe and Brazil recently (Marques et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…), and Kent Drops 20 ® (based on A. nilagirica, A. vulgaris Mattf., Dryopteris filix-mas Schott, and Tanacetum sp.). [16][17][18][19][20][21][22][23][24] In some of these studies, nematode-parasitized plants grew more when treated with the HP-an indication of enhanced tolerance to parasitism. Also, the HP may reduce nematode reproduction-a measure of efficacy in nematode control.…”
Section: Introductionmentioning
confidence: 99%
“…Indian research groups have reported negative effects of Cina Hepper). [4][5][6][7][8] These studies have reported reduction of nematode reproduction and less nematode damage to plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…), and Kent Drops 20 (Kent Homoeopathic Pharmacy, Pakistan) on Meloidogyne incognita (Kofoid and White) Chitwood and on Meloidogyne javanica (Treub) Chitwood, parasitizing sunflower, tomato, mulberry, okra (Abelmoschus esculentus [L.] Moench), mung bean (Vigna radiata [L.] R. Wilczek), and mash bean (V. mungo [L.] Hepper). [4][5][6][7][8] These studies have reported reduction of nematode reproduction and less nematode damage to plant growth.…”
Section: Introductionmentioning
confidence: 99%